Edukasi, Budidaya dan Pemanfaatan Tanaman Obat yang Berada di Sekitar Kita: Education, Cultivation and Utilization of Medicinal Plants that are Around Us - Siregar, Mirawati; Pahriyani, Ani; Sulistyaningsih, Endang (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Green meniran plants and Chinese betel leaves are medicinal plants that are widely used by the community. This activity aims to educate the public regarding the correct use of medicinal plants, their benefits, processing, and cultivation methods. The training implementation method is carried out by providing counseling and direct observation of sample plants and how they are processed. To measure success, namely collecting pre-test and post-test data, allowing researchers to measure participants' knowledge before and after health education. The results of the activity show that the level of knowledge of the elderly increased after taking part in the event as seen from the results of the correct scores on the post-test. The participants' knowledge increased because apart from providing education in the form of counseling, it was accompanied by direct identification of plants from samples provided by the team.